“Two Pillars Of Sustainability”: Pemberdayaan Pendidikan Dan Lingkungan, Serta Pertumbuhan Ekonomi Daerah Melalui Perspektif Social Humanity - Deswari Ayu Putri; Reina Delvira; Aldiat Noverza; Rozi (Universitas Bangka Belitung, 2023)
The humanitarian project in the 2023 of MBKM program is an activity concept designed to make